Urgensi Manajemen Pendidikan dalam Birokrasi dan Perkembangan Sistem Pendidikan di Indonesia - Marco Antonio; Arifin Yusli; Roby Priambodo (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This journal is written by taking into account the need for good management skills in the formulation of a good education system and how the system works as a bureaucracy. Given how important good management skills are to create a good system, this journal is made by looking at the existing reality of how the system itself is. Good management will create a good education bureaucracy, and a good bureaucracy will also produce a good education management system, and this will have an impact on improving the quality of education. In this journal, we try to open the reader's way of thinking about the urgency of good management in the education bureaucracy and the education system.